Full-color dynamic volumetric displays with tunable upconversion emission from RE3+-doped glasses (RE = Ho, Tm, Nd, Yb) under NIR laser excitation - Utku Ekim; Diğdem Özkutay; Miray Çelikbilek Ersundu; Ali Erçin Ersundu (Light: Science & Applications)
Abstract Three-dimensional (3D) imaging technology holds immense potential across various high-tech applications; however, current display technologies are hindered by limitations such as restricted viewing angles, cumbersome headgear, and limited multi-user accessibility. To address these challenges, researchers are actively exploring new materials and techniques for 3D imaging. Laser-based volumetric displays (VDs) offer a promising solution; nonetheless, existing screen materials fall short in meeting key requirements for long-term durability, full-color operation, and scalability. In this study, we present a comprehensive investigation into easily scalable rare-earth (RE3+) doped monolithic glasses (RE = Ho, Tm, Nd, Yb) capable of tunable full-color emission using a novel excitation modulation technique under 808 nm and 980 nm laser excitation and demonstrate their implementation as laser-based VD materials through prototyping. By controlling the movement of lasers’ pulses and galvanometer mirrors with waveform generators, our system generates images in simple and complex shapes with high purity red, green, and blue (RGB) colors. These images can be manipulated, including actions like translation, rotation, expansion, and sequential movement within the monolithic glass screen material. Our findings showcase the potential of glass-based dynamic VDs in revolutionizing display technology, offering superior color purity, vividness, and performance in comparison to conventional display systems.